PIN1-SUMO2/3 motif suppresses excessive RNF168 chromatin accumulation and ubiquitin signaling to promote IR resistance - Anoop S. Chauhan; Matthew J. W. Mackintosh; Joseph Cassar; Alexander J. Lanz; Mohammed Jamshad; Hannah L. Mackay; Alexander J. Garvin; Alexandra K. Walker; Satpal S. Jhujh; Teresa Carlomagno; Aneika C. Leney; Grant S. Stewart; et al. (Nature Communications)
Abstract RNF168 is an E3 ubiquitin ligase critical to the mammalian DNA double-strand break repair response. The protein is recruited to and amplifies ubiquitin signals at damaged chromatin and, if not properly regulated, can drive an uncontrolled ubiquitin cascade potentially harmful to repair outcomes. Several indirect mechanisms restrict RNF168 positive feedback, and a longstanding question has been whether these alone suppress excessive RNF168 signaling or whether mechanisms to remove RNF168 from damaged chromatin exist. Here, we reveal a cascade of post-translational modifications which act at three adjacent amino acids, threonine-208, proline-209 and lysine-210, to process RNF168 actively. Phosphorylation at threonine-208 by CDK1/2 induces interaction with the peptidyl-prolyl isomerase PIN1. PIN1 promotes RNF168 SUMOylation at lysine-210, resulting in p97/VCP mediated removal. These actions promote RNF168 clearance and limit RNF168 chromatin build-up. Thus, single amino acid substitutions of the regulatory motif (SUMO-PIN1-assisted Chromatin Regulator, SPaCR) that restrict PIN1 interaction or SUMOylation are sufficient to drive supraphysiological accumulation of RNF168, increased ubiquitin signaling, excessive 53BP1 recruitment and radiosensitivity. Our findings define a mechanism of direct RNF168 regulation that is part of the normal damage response, promoting RNF168 dissociation from chromatin and limiting deleterious ubiquitin signaling.